Analisis Keberhasilan Usaha Pada Usaha Kuliner di Kecamatan Baturaja Timur - Risma Krisdiana; Dahlia (Politeknik Negeri Sriwijaya, 2021)
This study aims to determine the effect of creativity and business motivation on business success in culinary businesses in East Baturaja District. The sample is 34 restaurant business units. The results showed that there was an influence of creativity (X1) and business motivation (X2) on business success (Y) either partially or simultaneously. The results of the simultaneous hypothesis test or f test can be that creativity has a greater influence on business success so that the most influential variable on business success is creativity. The results of the analysis of all indicators on the creativity variable there are indicators that have high values, namely being challenged to existing conditions, always curious, and having high self-motivation, while from the indicators of business motivation variables that there are indicators that have high values, namely material motivation.